Managing clustering effects and learning effects in the design and analysis of randomised surgical trials: a review of existing guidance - Conroy, EJ; Blazeby, JM; Burnside, G; Cook, JA; Gamble, C (BioMed Central, 2022)
Background: The complexities associated with delivering randomised surgical trials, such as clustering effects, by centre or surgeon, and surgical learning, are well known. Despite this, approaches used to manage these complexities, and opinions on these, vary. Guidance documents have been developed to support clinical trial design and reporting. This work aimed to identify and examine existing guidance and consider its relevance to clustering effects and learning curves within surgical trials.